Model Pembelajaran Cooperative Learning - Sumilat, Juliana Margareta; Supit, Putri; Sinombor, Victor Martino; Mewengkang, Daniela Veoni; Sambenaung, Keren (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine (1) learning planning using the cooperative learning model at the GMIM VI TOMOHON elementary school, (2) implementing learning using the cooperative learning model at the GMIM VI TOMOHON elementary school, (3) evaluating learning using the cooperative learning model at the GMIM elementary school. VI PLEASE. This research is a case study and the object of this research is learning planning, learning implementation, and learning evaluation using the cooperative learning model. The research subjects were elementary school children, teachers and school principals. Data collection used used methods (1) observation, (2) interviews, (3) and documentation. The results of this research show that (1) the learning planning for the observation report text using the cooperative learning model is in accordance with learning based on the characteristics of the cooperative learning method and is also in line with the provisions of the Merdeka Curriculum, but it is necessary to add learning resources that are appropriate to the learning, learning media should be adapted to the characteristics students (2) the learning implementation is carried out in accordance with the learning scenario based on the characteristics of the cooperative learning model, but there are things that are still missing, namely apperception and utilization of allocations, (3) the learning evaluation is in accordance with the principles of the cooperative learning method. However, there are some things that still escape the attention of teachers, namely the question instructions and the range of scores on the questions